SOMANZ Guidelines for the Investigation and Management of Sepsis in Pregnancy. Issue 3 (September 2018) - Bowyer, L.; Robinson, H.L.; Barrett, H.; Crozier, T.M.; Giles, M.; Idel, I.; Lowe, S.; Lust, K.; Marnoch, C.A.; Morton, M.R.; Said, J.; Wong, M.; et al.
Abstract : ( Aust N Z J Obstet Gynaecol 2017;57:540–551) Sepsis, caused by Group A beta hemolytic streptococcal (GAS) infection, is an increasing cause of maternal mortality in both Australia and the United Kingdom. Sepsis can lead to insufficiency in maternal circulation, leading to compromised fetal perfusion and fetal distress. The Society of Obstetric Medicine of Australia and New Zealand (SOMANZ) has designed evidence-based guidelines for the effective investigation and management of sepsis in pregnant and postpartum women.